2022
DOI: 10.53293/jasn.2022.4073.1137
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Study of Denture Base Resin Poly(Methyl Methacrylate) Reinforced by ZnO and TCP Nanoparticles

Abstract: Denture base poly (methyl methacrylate (PMMA) resin is one of the most frequently used materials in denture base synthesis, but due to its poor mechanical properties, PMMA can be considered a medium for the attachment and growth of a variety of pathogenic bacteria and fungi, particularly due to PMMA's pores and rough surface. The porosity percentage and surface roughness of the PMMA resin sample was lowered in this study, which resulted in a reduction in microorganisms' surface adhesion by varying the ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…(1) Since 1937, acrylic resins have been the most widely utilized material in the production of denture bases. (2) It is superior to other materials since it is simple to work with and repair, nontoxic, and lightweight, but it has a number of disadvantages, one of which is that it has subpar mechanical qualities. (3) A denture fracture results from two different types of forces, namely impact and flexural fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Since 1937, acrylic resins have been the most widely utilized material in the production of denture bases. (2) It is superior to other materials since it is simple to work with and repair, nontoxic, and lightweight, but it has a number of disadvantages, one of which is that it has subpar mechanical qualities. (3) A denture fracture results from two different types of forces, namely impact and flexural fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes demonstrated that the qualities of wear, tensile, and thermal properties were enhanced by the addition of licorice and pomegranate particles to poly methyl methacrylate resin. (2) In 2021, Teba et al published an paper about enhancing the mechanical properties of heat cured acrylic resin by adding the natural sisal fibers powder. 90 specimens were prepared for use in her investigation.…”
Section: Introductionmentioning
confidence: 99%